Effectiveness of UMKM Competitiveness Policies in the Digital Age - Adelia, Kania Destriawati; Khumayah, Siti (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study examines the effectiveness of MSME competitiveness enhancement policies implemented by the DKUKMPP of Cirebon City in the context of accelerating digital transformation. Using Thomas R. Dye’s public policy theory as the analytical framework, the research employs a descriptive qualitative case study method with data collected through in-depth interviews, field observations, and documentation of officials and MSME actors involved in the digitalization program. Findings show that policies such as digital marketing training, e-commerce assistance, and licensing digitization have generated positive administrative outputs, yet substantive outcomes—including improved digital behavior, technological literacy, and market expansion—remain uneven. Key challenges include unequal access to resources, low digital literacy, limited bureaucratic competence, and communication strategies that lack inclusivity. The study concludes that policy effectiveness depends on multi-actor collaboration, equitable resource distribution, strengthened implementer capacity, and adaptive implementation models aligned with local social contexts.